Neurorehabilitation and its impact on functional status in patients who have suffered a stroke - Salselas, Susana (2022)
Stroke represents the main cause of functional dependence and in the Portuguese adult population. Objective: To analyse the impact of rehabilitation on functional state and basic activities of daily life (ABVD), 8 weeks following a stroke, in a population of elderly people in north-western Portugal. Methodology: Observational, longitudinal and retrospective study. The patients were grouped into 3 groups according to the rehabilitation treatment received: non-rehabilitation (NR), light rehabilitation (RL) and intense rehabilitation (RI). Sociodemographic data, clinical variables (on stroke), hospital stay, rehabilitative treatment, and functional status (Barthel index) were collected. Results: 350 patients, with a mean age of 75.83 (± 8.02) years. The hospital stay was longer in the group of RL (19.7 [± 8.69]), RI (17.67 [± 10.05]) and of those who did not undergo rehabilitation (10.97 [± 6.96]) (P = .001). A significant increase (P < .001) was observed in the Barthel index scores from admission to 8 weeks after the stroke. Age (P = .003) and hospital stay (P = .013) were shown as risk factors for functional dependence. Similarly, taking as a reference the patients who did not undergo rehabilitation, the subjects who underwent light rehabilitation (OR: 6.37; 95% CI: 1.74-23.25; P = .005) and intensive rehabilitation (OR: 2.28; 95% CI: 1.08-4.82; P = .030), had a significantly higher risk of presenting functional dependence Conclusion: Undergoing intensive rehabilitation improves functional state and ABVD compared to light rehabilitation, 8 weeks following a stroke in elderly patients.